Association of Head and Neck Cancers in Chronic Osteomyelitis: A National Retrospective Cohort Study. Issue 3 (January 2016) - Tsai, Chia-Ta; Ho, Mao-Wang; Lin, Dana; Chen, Hsuan-Ju; Muo, Chih-Hsin; Tseng, Chun-Hung; Su, Wen-Chi; Lin, Ming-Chia; Kao, Chia-Hung
Abstract : Abstract: The aim of study is to determine whether chronic osteomyelitis (COM) is linked to an increased risk of head and neck cancer (HNC). We identify 17, 033 patients with osteomyelitis and 68, 125 subjects without osteomyelitis during 1996 to 2010 periods. Multivariable Cox proportional hazards regression analysis was used to measure the hazard ratio (HR) of head and neck cancer for the osteomyelitis cohort compared with the comparison cohort. A total of 99 patients in the COM and 228 patients in the comparison cohort developed HNC during an average 5.12 years of follow-up period. The incidence rate of HNC in the COM cohort was 1.51-fold (95% confidence interval [CI]: 1.17–1.95) higher than that in the comparison cohort after adjusting gender, age, urbanization level, monthly income, and comorbidities. In subgroup analysis, younger (less than 45 years-old) and patients without comorbidities have greater risks (adjusted HR: 2.29 [95% CI:1.43-3.66] and 1.74 [95% CI:1.28-2.38] respectively). This study results suggested the association between COM and HNC, particularly in younger population and patients without comorbidities.